(untitled) (Ukrainian Journal of Ophthalmology, 2024)
The ‘uveitis masquerade syndrome’ is a large group of neoplastic and non-neoplastic conditions that mimic and are initially misdiagnosed as uveitis. These eye diseases account for approximately 5% of all presentations at tertiary referral uveitis clinics. Vitreoretinal lymphoma is one of the most common of the neoplastic conditions that present as uveitis. With a 5-year survival rate under 50%, it is vitally important to recognize this diagnosis promptly. Other malignancies that may masquerade as uveitis include systemic lymphomas, primary uveal lymphoma, leukemias, multiple myeloma, uveal melanoma, metastatic cancers, and in children, retinoblastoma, medulloepithelioma, and post-transplantation lymphoproliferative disorder. Paraneoplastic syndromes are also possible uveitis mimics. Non-neoplastic conditions that may present as uveitis include the ocular ischemic syndrome and other vascular eye diseases, central serous chorioretinopathy, inherited retinal diseases, rhegmatogenous retinal detachment, pigment dispersion syndrome, intraocular foreign bodies, and in children, juvenile xanthogranuloma and Coats disease. In this article, we review the uveitis masquerade syndrome. Our major focus is vitreoretinal lymphoma, but we also summarize the other neoplasms and non-neoplastic diseases that may masquerade as uveitis.